The Effect Of Frequency Tuba Root Extract Applications (Derris elliptica Benth.) On The Pest Of Brown Planthopper (Nilaparvata lugens Stal.) in Rice Plants (Oryza sativa L.) - Nurjayanti NJ Nurjayanti; Rusli RR Rustam; Hafiz NF Fauzana (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Rice plants are plagued by the brown planthopper (Nilaparvata lugens Stal.). Synthetic pesticides are commonly used in pest control, which have negative consequences such as secondary pest explosions, resistance, natural enemy death, revival, and contamination. As a result, a pest-control alternative is required, namely the use of vegetable pesticides derived from tuba roots (Derris elliptica Benth.). The study's goal was to see how effective tuba root extract combined with organic solvents was at controlling brown planthoppers on rice plants in greenhouses at various spraying intervals. Plant Pest Laboratory and Technical Implementation Unit for Experimental Gardens, Postgraduate Agricultural Sciences, Faculty of Agriculture, Riau University, conducted the study. To acquire 20 experimental units, the investigation was conducted experimentally utilizing a Completely Randomized Design (CRD) with four treatments and five replications. Without spraying tuba root extract, spraying tuba root extract 1x1 week, 1x2 weeks, and 1x3 weeks were the treatments used. Spraying tuba root extract once a week was the most effective interval, as it reduced the brown planthopper nymph population to 38.20 imagos per clump, the imago population to 31.80 individuals per clump, and the attack intensity to 24 percent.